2009
DOI: 10.1186/cc7765
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastometry for the assessment of coagulation abnormalities in early and established adult sepsis: a prospective cohort study

Abstract: Introduction The inflammatory response to an invading pathogen in sepsis leads to complex alterations in hemostasis by dysregulation of procoagulant and anticoagulant factors. Recent treatment options to correct these abnormalities in patients with sepsis and organ dysfunction have yielded conflicting results. Using thromboelastometry (ROTEM ® ), we assessed the course of hemostatic alterations in patients with sepsis and related these alterations to the severity of organ dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
78
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 45 publications
11
78
1
6
Order By: Relevance
“…Typical hypocoagulable tracing was not found in the whole group on admission, possibly because a major increase in fibrinogen level compensated for the decreased platelet count and other consumed factors. Our findings in septic shock are consistent with previous reports of ROTEM in patients with severe sepsis demonstrating either hyper- [28], normo- [26,29], or hypocoagulability [29,31], the last of these generally being observed in more severe cases. Our ROTEM results also demonstrated hypofibrinolysis, as classically reported in sepsis and already documented by ROTEM in severe sepsis [30].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Typical hypocoagulable tracing was not found in the whole group on admission, possibly because a major increase in fibrinogen level compensated for the decreased platelet count and other consumed factors. Our findings in septic shock are consistent with previous reports of ROTEM in patients with severe sepsis demonstrating either hyper- [28], normo- [26,29], or hypocoagulability [29,31], the last of these generally being observed in more severe cases. Our ROTEM results also demonstrated hypofibrinolysis, as classically reported in sepsis and already documented by ROTEM in severe sepsis [30].…”
Section: Discussionsupporting
confidence: 82%
“…TG has been reported as a useful tool to guide therapy in patients with hemophilia [23] and to detect hypercoagulability in patients with unprovoked venous thromboembolism [24] and type 2 diabetes [25]. A few studies reported TG [26,27], TEG [28], or ROTEM [26,[29][30][31] measurements in adults with severe sepsis but none in septic shock. We hypothesized that septic shock induces a coagulopathy early in its course that could be revealed by these new global coagulation tests, and that the severity of the coagulopathy in septic shock is associated with greater mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Similar changes in clot formation, which were accompanied by a decrease in plasma fibrinogen level, have been shown in rats 6 h after endotoxin administration [26,27]. The decrease in hemostatic potential in the animal models reported here and elsewhere is in contrast to data obtained in clinical studies where sepsis, at least in its early state, was associated with hypercoagulability with an increase in clot formation rate and maximum clot firmness [28][29][30]. Thus, the question arises as to whether sepsis in rodents does not result in hypercoagulability, or whether hypercoagulability quickly switches to a hypocoagulable state owing to consumption of clotting factors.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, thromboelastometry (TEM) and thrombelastography (TEG ® ) represent the only bedside methods, which also provide information about the changes in the fibrinolytic system (17,18). However, reports on the use of TEM/TEG as a point-of-care monitoring device in sepsis and DIC are rare (16,19,20,21). Collins et al (16) observed that compared with normal controls, critically ill patients with sepsis syndrome had a prolonged CT, increased α angle and increased MCF.…”
Section: Discussionmentioning
confidence: 99%